2016
DOI: 10.1111/gcbb.12316
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem model parameterization and adaptation for sustainable cellulosic biofuel landscape design

Abstract: Renewable fuel standards in the US and elsewhere mandate the production of large quantities of cellulosic biofuels with low greenhouse gas (GHG) footprints, a requirement which will likely entail extensive cultivation of dedicated bioenergy feedstock crops on marginal agricultural lands. Performance data for such systems is sparse, and non-linear interactions between the feedstock species, agronomic management intensity, and underlying soil and land characteristics complicate the development of sustainable lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 124 publications
(149 reference statements)
1
24
0
1
Order By: Relevance
“…Calibration of the DAYCENT model for switchgrass (lowland ecotype) has already been achieved and has been evaluated for both Unites States and Europe environments in our previous work (Field et al., ; Nocentini, Di Virgilio, & Monti, ). To obtain the parameterization of the model for giant reed, besides using field data from our own long‐term experiments in North Italy (Alexopoulou et al., ; Monti & Zegada‐Lizarazu, ), a literature research has been carried out to select those studies which reported significant information on giant reed's aboveground and below‐ground C pools.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Calibration of the DAYCENT model for switchgrass (lowland ecotype) has already been achieved and has been evaluated for both Unites States and Europe environments in our previous work (Field et al., ; Nocentini, Di Virgilio, & Monti, ). To obtain the parameterization of the model for giant reed, besides using field data from our own long‐term experiments in North Italy (Alexopoulou et al., ; Monti & Zegada‐Lizarazu, ), a literature research has been carried out to select those studies which reported significant information on giant reed's aboveground and below‐ground C pools.…”
Section: Methodsmentioning
confidence: 99%
“…To simulate the mature phase, the prdx value was set lower (0.225) to reduce the yield capacity of giant reed. The sfnxmx (1) parameter was set slightly higher than 0 (Field et al., ), only to simulate switchgrass and giant reed capacity to achieve considerable yields without N fertilization (Alexopoulou et al., ; Monti & Zegada‐Lizarazu, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ecosystem process‐based models have been applied for spatially explicit bioenergy sustainability assessment for more than a decade (Sheehan et al ., ). Modern high‐power computing enables ecosystem model application at the requisite fine spatial scales (Nichols et al ., ) either through thousands of independent runs of ‘point’ models, for example DayCent (Davis et al ., ; Yu et al ., ; Field et al ., ) and EPIC (Zhang et al ., ; Gelfand et al ., ) or using ‘network’ models (e.g. SWAT; Wu et al ., ; Gramig et al ., ) that consider lateral hydrological or biogeochemical flows between networks of thousands of nodes.…”
Section: Statement 6: Ecosystem Process‐based Models Are Essential Fomentioning
confidence: 99%
“…The environmental drivers of N 2 O and CH 4 emissions are largely unknown, and observations of the fluxes of these gases produce varying results (Harris et al, ). Former land use, site‐specific soil properties and climate conditions influence GHG emissions from SRCs (Field, Marx, Easter, Adler, & Paustian, ; Whitaker et al, ). Site management, that is, the use of fertilizer, irrigation, and length of the rotation period, also influences the GHG balance (Carter et al, ; Díaz‐Pinés et al, ).…”
Section: Introductionmentioning
confidence: 99%